The causal power of social structures : emergence, structure and agency - Elder-Vass, Dave (Cambridge : Cambridge University Press, 2010)
The problem of structure and agency has been the subject of intense debate in the social sciences for over 100 years. This book offers a solution. Using a critical realist version of the theory of emergence, Dave Elder-Vass argues that, instead of ascribing causal significance to an abstract notion of social structure or a monolithic concept of society, we must recognise that it is specific groups of people that have social structural power. Some of these groups are entities with emergent causal powers, distinct from those of human individuals. Yet these powers also depend on the contributions of human individuals, and this book examines the mechanisms through which interactions between human individuals generate the causal powers of some types of social structures. The Causal Power of Social Structures makes particularly important contributions to the theory of human agency and to our understanding of normative institutions.
Introduction. The problem of structure and agency ; Emergence and social structure ; How to read this book ; Critical realism -- Emergence. Relational emergence ; Strong enterprise ; Morphogenesis and morphostasis ; Conclusion -- Cause. Covering law theories of causality ; Realism and casual power ; Actual causation ; Reductionism ; Downward causation ; Conclusion -- Social ontology and social structure. The elements of emergence ; A method for social ontology ; Applying the method ; Social structure ; Three facets of social structure ; What kind of structural element is social structure? ; Four concepts of social structure ; Conclusion -- Agency. The emergence of the mental ; An emergentist theory of action ; Bourdieu's habitus ; Archer versus Bourdieu ; Synthesising Archer and Bourdieu ; Conclusion -- Normative institutions. Theories of social institutions ; Norm circles ; Norm circle boundaries ; Intersectionality between normative circles ; Change in social institutions ; Institutions and structuration theory ; Conclusion -- Organisations. Interaction groups ; Associations ; The casual power of organizations ; Individuals in organisations ; Authority and organisations ; Organisations and institutions ; Conclusion -- Social events. A micro-social interaction ; Micro-social explanations ; From micro to macro ; Macro-actors and macro-consequences ; Collective macro-events ; Statistical macro-events : Durkheim and suicide ; Conclusion -- Conclusion. The casual power of social structures ; For and against naturalism ; The spatial disarticulation of social structures ; An agenda for research.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Social structure; Causation